2017
DOI: 10.1021/acscatal.7b01330
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Regioselective Decarboxylative/C–H α-Alkoxyalkenylation of Heterocycles Using α-Carboxyvinylethers

Abstract: A direct introduction of vinyl ethers into C–H bond of heterocycles is reported. For this purpose, decarboxylative direct C–H cross-coupling of 1,3-diazoles with α-carboxyvinyl ethers as coupling partners was achieved under Pd(0)/Cu­(I) cooperative catalysis to produce various α-heteroarylated vinylethers. This methodology was applied to the innovative production of heteroarylated enolizable ketones and naturally occurring bis-oxa­(thia)­zoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 121 publications
0
17
1
Order By: Relevance
“…3), and (2) to give access to several synthetically‐challenging building blocks. Indeed, our group has recently reported the first regio‐ and stereocontrolled formation of α‐heteroarylated enol ethers I by Pd‐catalyzed decarboxylative C–H coupling of α‐alkoxyacrylic acid derivatives, as well as the synthesis of ( Z )‐β‐arylated enol ethers II by copper mediated protodecarboxylation reactions . Herein, Pd II ‐catalyzed decarboxylative Heck coupling of α‐alkoxyacrylates with (hetero)aryl carboxylic acids for the stereocontrolled production of ( Z )‐β‐heteroarylated vinyl ethers is reported (Figure , Equ.…”
Section: Introductionmentioning
confidence: 99%
“…3), and (2) to give access to several synthetically‐challenging building blocks. Indeed, our group has recently reported the first regio‐ and stereocontrolled formation of α‐heteroarylated enol ethers I by Pd‐catalyzed decarboxylative C–H coupling of α‐alkoxyacrylic acid derivatives, as well as the synthesis of ( Z )‐β‐arylated enol ethers II by copper mediated protodecarboxylation reactions . Herein, Pd II ‐catalyzed decarboxylative Heck coupling of α‐alkoxyacrylates with (hetero)aryl carboxylic acids for the stereocontrolled production of ( Z )‐β‐heteroarylated vinyl ethers is reported (Figure , Equ.…”
Section: Introductionmentioning
confidence: 99%
“…The various (Z/E)-α-fluroacrylic acids successfully delivered the Z/E-isomeric products in good to moderate yields with good functional group tolerance (Scheme 35). Later in 2017, the same group developed a decarboxylative C-H alkenylation of various azoles with α-alkoxylated acrylic acids [65]. This decarboxylative coupling proceeded smoothly employing [Pd(acac)2] as catalyst along with CuCO3.Cu(OH)2.…”
Section: Decarbonylative C-h Alkenylationmentioning
confidence: 99%
“…Using these optimized conditions, the authors successfully reported a convenient approach to generate α,β-enolizable α-ketoazoles and biologically active C2−C4′ linked azoles. Later in 2017, the same group developed a decarboxylative C-H alkenylation of various azoles with α-alkoxylated acrylic acids [65]. This decarboxylative coupling proceeded smoothly employing [Pd(acac) 2 ] as catalyst along with CuCO 3 .Cu(OH) 2 .…”
Section: Scheme 34 Ni-catalyzed Decarbonylative C-h Alkenylation Of Various Azolesmentioning
confidence: 99%
“…(20a): [20] Following procedure A, from 2-bromonaphthalene (0.207 g, 1 mmol) and oxazole (0.138 g, 2 mmol), product 20a was obtained in 55% yield (0.107 g) as an orange solid: mp 116-118 °C.…”
Section: -(Naphthalen-2-yl)oxazolementioning
confidence: 99%